The THE THRILL OF THE CLIMB: NEED FOR ACHIEVEMENT: Sensasi Dari Sebuah Pendakian: Kebutuhan Berprestasi - Efrata Putri, Anatasya Rahmawati Dyah; Taufik Akbar Rizqi Yunanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Need for achievement is an inner drive possessed by individuals to achieve the desired goals. The theory used in this study is David McCelland's theory with the need for achievement theory (1971). The purpose of this study was to determine the dynamics and description of need for achievement in SMP X Surabaya students.This research used a qualitative study approach. The choice of method and design is in accordance with the research objectives, namely to explore the need for achievement from the subject's point of view along with the dynamics that arise in the data collection process. The results of this study indicate that both subjects have a high need for achievement, because they have aspects of need for achievement and are followed by several attitudes such as self-confidence, gratitude, the role of spirituality, positive meaning and so on.There are several factors that make both subjects have a need for achievement, including having class goals and being balanced with productive activities so that they can make both subjects become empowered. Not only that, the attitude of a champion's heart is also determined by having an unyielding attitude, a hardy person, self-confidence, and having a sense of gratitude. Such a big push makes both subjects also have a need for achievement.